2020
DOI: 10.3389/fimmu.2020.01788
|View full text |Cite
|
Sign up to set email alerts
|

MAIT Cells at the Fetal-Maternal Interface During Pregnancy

Abstract: One of the main functions of the human placenta is to provide a barrier between the fetal and maternal blood circulations, where gas exchange and transfer of nutrients to the developing fetus take place. Despite being a barrier, there is a multitude of crosstalk between maternal immune cells and fetally derived semi-allogeneic trophoblast cells. Therefore, the maternal immune system has a difficult task to both tolerate the fetus but at the same time also defend the mother and the fetus from infections. Mucosa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 79 publications
0
22
0
Order By: Relevance
“…Mucosal-associated invariant T (MAIT) cells are antimicrobial T cells able to recognize bacterial metabolites and can function as innate-like sensors and mediators of antiviral responses, playing also a role in the response to anticancer therapy 32 . MAIT cells accumulate at term pregnancy in the maternal blood that flows into the intervillous space inside the placenta, where they are recruited by chemotactic factors 33 . Patients with active COVID-19 infection displayed a decrease in circulating MAIT cell compartment that is characterized by strong activation 34 .…”
Section: Resultsmentioning
confidence: 99%
“…Mucosal-associated invariant T (MAIT) cells are antimicrobial T cells able to recognize bacterial metabolites and can function as innate-like sensors and mediators of antiviral responses, playing also a role in the response to anticancer therapy 32 . MAIT cells accumulate at term pregnancy in the maternal blood that flows into the intervillous space inside the placenta, where they are recruited by chemotactic factors 33 . Patients with active COVID-19 infection displayed a decrease in circulating MAIT cell compartment that is characterized by strong activation 34 .…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, the local cell-to-cell concentrations may be higher than currently measurable levels, which could explain why most often supra-physiological concentrations are used in vitro. Furthermore, circulating maternal immune cells are sequestered in the placenta where they come in close contact with hormone-producing fetally-derived cells ( 67 ) and thus, have the potential of being exposed to much higher levels of P4 than in the peripheral circulation.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we did not investigate functional responses of MAIT cells in 1 st trimester decidua. Studies on 3 rd trimester decidua showed MAIT cells to respond to bacterial challenge with the production of IFNγ, granzyme B and perforin, indicating potential involvement in antibacterial defenses ( 22 , 24 , 32 ). Given their tissue repair potential ( 8 ), also the transcriptional activity of MAIT cells would be relevant to investigate as well as their role in endometrial tissue remodeling during decidualization (in similarity to uterine NK cells).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, MAIT cells isolated from term decidua responded to bacterial challenge with production of IFNg, granzyme B and perforin at a similar magnitude as MAIT cells in peripheral blood (22). Furthermore, MAIT cells were found to be retained in the intervillous blood in term placenta; these cells responded to stimulation with the production of IFNg and cytotoxic effector molecules and could serve to defend the fetal-maternal interface from bacterial infections (22)(23)(24). In contrast, very little is known about MAIT cells in the early stage of pregnancy.…”
Section: Introductionmentioning
confidence: 99%